Seasonal and Diurnal Variations of Tropical Tropopause Layer (TTL) Over the Indian Peninsula. Issue 23 (8th December 2017) - Muhsin, M.; Sunilkumar, S. V.; Venkat Ratnam, M.; Krishna Murthy, B. V.; Parameswaran, K.
Abstract: Seasonal and diurnal variations in the thermal structure of the troposphere and lower stratosphere with special reference to the tropical tropopause layer (TTL) are studied using data from 3 h interval radiosonde launches carried out simultaneously from Trivandrum (8.5°N, 76.9°E) and Gadanki (13.5°N, 79°E) during December 2010 to March 2014. TTL is defined as the region extending from the level of minimum stability (LMinS) to the level of maximum stability (LMaxS). Above the cold point tropopause (CPT), temperature showed warm anomaly (4–5 K) during summer monsoon (June–September) and cold anomaly (up to −4 K) during winter (December–February). The temperature in the troposphere showed a clear diurnal variation (±0.5 K) with a cold anomaly during early morning and warm anomaly during the day in all the seasons. At Gadanki, the diurnal temperature anomaly in the lower stratosphere showed its phase propagating downward with time, whereas at Trivandrum such variations are not clearly evident. At diurnal timescales, the TTL showed significant variations at LMinS (0.5–1.5 km/5–7 K) and smaller variations at CPT (0.2–0.5 km/2–3 K). In general, the amplitude of the diurnal component is greater than the semidiurnal component for all the TTL parameters, and these amplitudes are relatively larger at Trivandrum than at Gadanki. The observed diurnal variations could be the manifestation of tidal oscillations and/or due to the influence of local convection. Correlation analysis between different TTL parameters indicated a slow transition from a governing adiabatic process in the TTL base to a diabatic process at the TTL top. Key Points: Diurnal variations are significant at the TTL‐base and are small at cold point tropopause (CPT) Amplitude of diurnal component is larger than the semidiurnal component Diurnal variation of TTL could be the manifestation of tidal oscillations and local convection